2012
DOI: 10.2337/dc11-1793
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trajectories of HbA1c and Fasting Plasma Glucose Levels During the Development of Type 2 Diabetes

Abstract: OBJECTIVETo describe the trajectory of HbA1c and glucose concentrations before the diagnosis of diabetes.RESEARCH DESIGN AND METHODSThe study comprised 1,722 nondiabetic Japanese individuals aged 26–80 years. Fasting plasma glucose (FPG) and HbA1c were measured annually for a mean of 9.5 (SD 1.8) years.RESULTSDiabetes occurred in 193 individuals (FPG ≥7.0 mmol/L, self-reported clinician-diagnosed diabetes, or HbA1c ≥6.5%). Mean HbA1c values were >5.6% each year before diagnosis in diabetes cases. Mean HbA1c (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 12 publications
9
52
0
Order By: Relevance
“…In those with a starting HbA 1c of ,6% (,42 mmol/mol), most of whom are likely to be on unchanging therapy, the slope of the relationship between testing frequency and change in HbA 1c (4% over 12 months; equivalent to a change from 5.5 to 5.7% [37 to 38.5 mmol/mol]) is consistent with the natural history of disease progression in such patients. Heianza et al (15) estimated the annual increase at ;0.09% (;1 mmol/mol) per year in nondiabetic patients 1-3 years prediagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In those with a starting HbA 1c of ,6% (,42 mmol/mol), most of whom are likely to be on unchanging therapy, the slope of the relationship between testing frequency and change in HbA 1c (4% over 12 months; equivalent to a change from 5.5 to 5.7% [37 to 38.5 mmol/mol]) is consistent with the natural history of disease progression in such patients. Heianza et al (15) estimated the annual increase at ;0.09% (;1 mmol/mol) per year in nondiabetic patients 1-3 years prediagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that biomarker trajectories preceding diabetes development for cases and non-cases diverge over time [92][93][94][95][96]. Such trajectories require blood samples to be taken over a wider timeframe (several years or decades).…”
Section: Lipids and Small Metabolitesmentioning
confidence: 99%
“…Such trajectories require blood samples to be taken over a wider timeframe (several years or decades). These curves enable a better understanding of the pathophysiological processes of diabetes development and have been described for fasting and postload glucose, HbA 1c , interleukin-1 receptor antagonist, adiponectin, alanine aminotransferase and triacylglycerols [92][93][94][95][96]. Deeper insight into the development of type 2 diabetes can also be expected from the analysis of established metabolic risk factors such as BMI, waist circumference, other lipids or uric acid, for which multiple measurements in the same patients over time are usually available to the treating general practitioner.…”
Section: Lipids and Small Metabolitesmentioning
confidence: 99%
“…Since the diagnostic criterion of HbA 1c ≥6.5% (48 mmol/mol) has been newly introduced not only by the ADA but also by the World Health Organization [32], the utility of HbA 1c testing as a screening tool to predict future diabetes, especially estimating risk among individuals below the diagnostic threshold of 6.5% (48 mmol/mol), should be considered. In our previous study, we observed that elevations in the glycaemic markers FPG and HbA 1c were strongly predictive of the development of diabetes [33]. Therefore, it would be reasonable to consider whether their addition to other possible predictors would allow us to devise a simple, sensitive and specific algorithm to predict diabetes.…”
Section: Introductionmentioning
confidence: 99%